(untitled) (International Journal of Food and Nutritional Sciences, 2022)
DevOps has revolutionized software development by integrating development and operations teams, fostering collaboration, and automating processes to enhance efficiency. Traditional software development models often suffered from bottlenecks, miscommunication, and slow release cycles. DevOps addresses these challenges by promoting continuous integration, continuous delivery (CI/CD), automation, and real-time monitoring, leading to faster deployments, higher software quality, and improved system reliability. One of the primary impacts of DevOps is the acceleration of the software development lifecycle. By automating repetitive tasks such as testing, deployment, and infrastructure management, DevOps reduces manual effort, minimizes errors, and speeds up releases. This allows organizations to deliver software updates more frequently and reliably, ensuring quick responses to market demands and customer feedback. Additionally, DevOps enhances collaboration between teams by breaking down silos and encouraging shared responsibility. Developers and operations teams work together seamlessly, improving communication and reducing inefficiencies. Automation further optimizes processes by enabling early defect detection, infrastructure as code (IaC), and continuous monitoring, which enhances security, scalability, and system resilience.